circRNA18_46222157_46248185 inhibits melanogenesis by targeting miR-211/ pathway in goat melanocytes - Kai Yuan Ji; Xue Qing Zhang; Yi Wei Zhao; Chun E Liang; Xin Yuan; Yun Hai Zhang (Animal Bioscience)
Objective This study investigated the effects of circRNA18_46222157_46248185 (named circRNA18) on goat melanogenesis, which differs significantly in goat skins isolated from white and brown coat-colored skins. Methods Expression patterns of circRNA18 in goat skin and melanocytes were determined by quantitative real-time polymerase chain reaction (qRT-PCR) and in situ hybridization. The circRNA18 interference vector was designed and synthesized to transfect melanocytes and detect the effect of circRNA18 interference on melanin production. Bioinformatics software was used to predict the targeted adsorption miRNAs of circRNA18, verified by luciferase assay. A miRNA expression vector was constructed and transfected into melanocytes to detect the effect of miRNA on melanin production, and the targeted regulatory genes were detected by luciferase assay. Target gene interference vector was constructed to detect the influence of target gene interference on melanin production. Results qRT-PCR results unveiled distinct expression patterns of circRNA18 in diverse tissues of male and female goats, while in situ hybridization assays showed that circRNA18 is expressed in the cytoplasm of melanocytes. Functional analysis demonstrated that the downregulation of circRNA18 in melanocytes leads to a significant increase (p<0.01) in melanin production. Bioinformatics analysis identified a potential miR-211 binding site on circRNA18, and luciferase assay confirmed their interaction. Overexpression of miR-211 in melanocytes significantly augmented (p<0.01) melanin production. There were two potential miR-211 binding sites on adenoviral E1A-binding protein (EP300), and the overexpression of miR-211 in melanocytes significantly decreased (p<0.001) EP300 expression, with luciferase assay confirming their interaction. Downregulation of EP300 expression in melanocytes through siRNA-EP300 transfection results in a substantial increase (p<0.05) in melanin production. qRT-PCR results indicated that overexpression of mimics-circRNA18 in melanocytes markedly suppressed (p<0.0001) miR-211 expression, significantly elevated (p<0.01) EP300 expression, and significantly inhibited (p<0.001) melanin production. Conclusion circRNA18_46222157_46248185 acted as a negative regulator of melanogenesis in goat melanocytes by targeting the miR-211/EP300 pathway, and guiding animal hair color breeding strategies.